2015
DOI: 10.2139/ssrn.2697497
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Flow of Bilateral Adaptation-Related Climate Change Financing To Sub-Saharan African Countries

Abstract: The apparent mismatch between countries receiving Adaptation-related Climate Change Financing (ACCF) and those most vulnerable to climate change is a concern which is the motivation for this research. This paper examines the determining factors of receiving ACCF for sub-Saharan African countries and finds that the recipient policy and an existing aid relationship are significant determinants of funding. ACCF therefore appears to be contingent on democratic characteristics of the recipient and prevailing a dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…We now turn to the discussion of climate aid, and how this relatively new form of aid is allocated. Recent studies have shown that the three allocation models (recipient need, recipient merit, donor interests) are also of relevance in the realm of climate aid (Figaj, 2010), and individually for both adaptation aid (Betzold and Weiler, 2018; Michaelowa and Michaelowa, 2012; Robertsen et al, 2015; Robinson and Dornan, 2017; Weiler et al, 2018) and mitigation aid (Bagchi et al, 2016; Halimanjaya, 2015). In particular Weiler et al (2018) mention that adaption aid flows follow “very closely” the pattern of general aid flows to developing countries.…”
Section: Literature Review and Expectationsmentioning
confidence: 99%
“…We now turn to the discussion of climate aid, and how this relatively new form of aid is allocated. Recent studies have shown that the three allocation models (recipient need, recipient merit, donor interests) are also of relevance in the realm of climate aid (Figaj, 2010), and individually for both adaptation aid (Betzold and Weiler, 2018; Michaelowa and Michaelowa, 2012; Robertsen et al, 2015; Robinson and Dornan, 2017; Weiler et al, 2018) and mitigation aid (Bagchi et al, 2016; Halimanjaya, 2015). In particular Weiler et al (2018) mention that adaption aid flows follow “very closely” the pattern of general aid flows to developing countries.…”
Section: Literature Review and Expectationsmentioning
confidence: 99%
“…Several studies examine funding decisions of the multilateral Adaptation Fund; they conclude that the Adaptation Fund does not accord priority to vulnerable countries (Persson and Remling 2014;Remling and Persson 2015;Stadelmann et al 2014). Robertsen et al (2015) focus on bilateral aid from seven donors to sub-Saharan Africa. Their results similarly suggest that donors do not take into account vulnerability in their allocation decisions:…”
Section: The Political Economy Of (Adaptation) Aidmentioning
confidence: 99%
“…It focuses on capacity development of institutions and community representatives rather than communities in designing projects and programs (Biagini et al, 2012). Despite its focus on adaptation, the First Start Finance, for instance, allocates the fund mainly to mitigation rather than adaptation (Fransen et al, 2015) and prioritizes institutional strength of recipient country rather than vulnerability while funding adaptation (Barrett, 2014;Robertsen, Francken, & Molenaers, 2015).…”
mentioning
confidence: 99%